Preliminary Report on the Effect of Ketamine in Patients with Central Pain - Sylvie Rostaing-Rigatti; Pierre Cesaro; Jean-Paul N’Guyen; Jean-François Ejzenbaum; Bernard Pollin; Francis Bonnet (Pain Research and Management)
This preliminary open prospective study reports on the effect of ketamine, an N-methyl-D-aspartate (NMDA)-receptor noncompetitive antagonist, in five patients suffering from central poststroke pain (CPSP). Patients were evaluated at rest on a visual analogue scale (VAS) graded from 0 to 10. Pain measurement was repeated at 15 and 30 mins following intravenous administration of 0.15 to 0.25 mg/kg ketamine and then every 30 mins for 6 h. Pain evoked by light touch or cold stimulation was also measured in three patients at those times. Patients were monitored for arterial pressure, heart rate, sedation and side effects during the study. Ketamine provided a significant improvement in pain at rest and in evoked pain. A 51% to 84% decrease in the VAS score for pain at rest was observed within 60 to 180 mins. Satisfactory pain relief (more than 50% decrease in the VAS score) lasted for 150 to 210 mins. Two patients had a prolonged improvement over two or three days. Arterial pressure and heart rate did not change significantly. Mild or moderate sedation was noticed in all patients for 20 to 30 mins. These results suggest that blockade of NMDA receptors may provide pain relief in patients suffering from CPSP.